Doped Organic Micro‐Thermoelectric Coolers with Rapid Response Time (Adv. Electron. Mater. 12/2022). (9th December 2022) - Wang, Shu‐Jen; Wohlrab, Steve; Reith, Heiko; Berger, Dietmar; Kleemann, Hans; Nielsch, Kornelius; Leo, Karl
Abstract : Doped Organic Micro‐Thermoelectric Coolers The operation mechanism of doped organic Peltier cooling device is illustrated. Organic semiconductors offer unique opportunities for local cooling devices due to their intrinsic mechanical flexibility, light weight and biocompatibility and could enable novel device concepts for display and healthcare applications. More details can be found in article number 2200629 by Shu‐Jen Wang, Heiko Reith, Karl Leo, and co‐workers.